Non-Pharmacological Therapy For Adolescent Depression: Literature Review - Indra Maulana; Hesti , Hesti Platini (Jurnal Kesehatan Islam : Islamic Health Journal, 2023)
ABSTRACT Introduction: Adolescence is a period of transition between childhood and adulthood, characterized by biological, cognitive, and socio-emotional changes. Most adolescents have behaved more maturely as they have become aware of a new formal status, either at home or at school. Adolescents are at risk for depressive disorders due to their inability to deal with stress or pressure. To alleviate depression symptoms, pharmacological and non-pharmacological therapies can be used. The goal of this study was to conduct a literature review on non-pharmacological therapies for treating depression in adolescents. Methods: A literature review with the keywords "Teenagers," "Depression," and "Therapy" was used as the research method. Several search engines were used to find articles, including Google Scholar, PubMed, and Science Direct. which were published between 2016 and 2020. Article searches turned up 29,982 results. Following the evaluation, the remaining six articles were chosen for a literature review. Results and Discussion : Six non-pharmacological therapies were discovered to treat depression in adolescents based on a literature review. Music therapy, life writing therapy, bright light therapy, exercise, and behavioral health interventions, such as cognitive behavioral therapy and assertive training, can all be used. Conclusion: Music therapy, life writing therapy, bright light therapy, exercise, and behavioral health interventions, such as cognitive behavioral therapy and assertive training, are all effective treatments for depression. Keyword:Depression, Teenagers, Therapy